Generation of Switchable Chirp Waveforms in the Photonic Domain with Immunity to Dispersion-Induced Power Fading - Chaoqun Huang (MDPI AG, 2021)
A novel photonic approach to generating switchable multi-format chirp waveforms using a dual-drive dual-parallel Mach–Zehnder modulator (DD-DPMZM) is proposed and experimentally demonstrated. By properly controlling the bias voltage on the DD-DPMZM, different chirp RF waveforms, including the dual-, down-, and up-chirp waveforms, can be obtained when an RF signal and a chirp RF signal are injected into the modulator. A main feature of this approach is that it can eliminate chromatic dispersion-induced RF power fading, which is highly desired in distributed multi-functional radars based on radio over fiber. There is no polarization control and optical filtering in the given scheme, which also improves the stability and feasibility of the approach. An experiment successfully demonstrated the generation and switching of the multi-format chirp waveforms and the capability of immunity to dispersion-induced power fading.